THE CONCEPT OF “UNORGANIZED YOUTH” AND ITS CHARACTERISTICS (American Journal of Research in Humanities and Social Sciences, 2024)
This article reveals the concept of unorganized youth, the specifics of unorganized youth, as well as issues of improving work with unorganized youth.